Andragogy: Searching for Ways to Improve the Educational Process in Educational Institutions for Adults - Tymchuk, Liudmyla; Kovalenko, Inna; Vieilandie, Lilia; Prokofyeva, Lyubov; Rasskazova, Olha; Topolnyk, Yana (My University, 2022)
The topic of the article is relevant because at the present time there is a renewal of the education system and the search for ways to improve the learning process in educational institutions for adults continues. In the studies of educators in the 1920s in the conditions of keen discussions a wide range of organizational forms and methods of adult education was highlighted and scientifically substantiated. Traditional in the teaching of adults, as well as in school practice, was the classroom teaching system. Its basis was the usual forms of classroom work - lecture, conversation, discussion, debate, storytelling, etc. The purpose of the article is the study of ways to improve the learning process in educational institutions for adults in the works of domestic and foreign scientists, the study and presentation of organizational forms and methods of adult education; the description of the organization of independent work of students by performing their research tasks. An important place in schools for adults was given to organization of independent work of students through implementation of their research tasks - term papers, essays. The use of the method of excursions was also widespread, the issue of application of the method of staging in the practice of teaching adults was substantiated. Group, individual and self-educational forms of organization of education have also become widespread in adult schools.
Andragogy: Searching for Ways to Improve the Educational Process in Educational Institutions for Adults / L. Tymchuk, I. Kovalenko, L. Vieilandie, L. Prokofyeva, O. Rasskazova, Y. Topolnyk // Revista Românească pentru Educaţie Multidimensională, 2022. –Vol. 14. – Issue 1(Sup1). – P. 472–494
Keywords: аудиторна система, аудиторна робота, дальтон-план, план лабораторної роботи, самостійна робота студентів, метод екскурсії, метод інсценізації; classroom system, classroom work, Dalton plan, laboratory plan, independent work of students, the method of excursions, the method of staging